2022
DOI: 10.1177/10711007211064600
|View full text |Cite
|
Sign up to set email alerts
|

Cavovarus With a Twist: Midfoot Coronal and Axial Plane Rotational Deformity in Charcot-Marie-Tooth Disease

Abstract: Background: The cavovarus deformity of Charcot-Marie-Tooth (CMT) disease is often characterized by a paradoxical relationship of hindfoot varus and forefoot valgus. The configuration of the midfoot, which links these deformities, is poorly understood. Accurate assessment of 3-dimensional alignment under physiologic loadbearing conditions is possible using weightbearing computed tomography (WBCT). This is the first study to examine the rotational deformity in the midfoot of CMT patients and, thus, provide key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The method was previously validated in the foot and ankle literature. 1,6,9,17,18 As far as we know, this is the first study investigating perioperative WBCT findings in CMT feet using automated 3D measurements. Another major strength of this study is the relatively large number of CMT patients that were included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method was previously validated in the foot and ankle literature. 1,6,9,17,18 As far as we know, this is the first study investigating perioperative WBCT findings in CMT feet using automated 3D measurements. Another major strength of this study is the relatively large number of CMT patients that were included.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the talonavicular joint in the axial correction of CMT deformity is well established in the literature. An et al 1 reported that CMT patients demonstrated increased axial plane adduction and coronal plane supination at the talonavicular joint, compared with healthy control cases. This may be attributable to chronic overpull of the posterior tibial tendon on the navicular, with inadequate, weakened abduction force by the peroneus brevis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This axial plane imbalance is a major contributor to the characteristic twisting, supination deformity of the midfoot. 14 The first step of surgical treatment is to address PT contracture by releasing the tendon from its insertion, even if it has inadequate strength for transfer. It is invariably contracted and a deforming force.…”
Section: Soft-tissue Releasesmentioning
confidence: 99%
“…The radiological evaluation of cavus foot should also include the Coleman block test in order to assess the flexibility of the foot. In the recent literature, Dr. Michalski [36] and Dr. Tonya An [37] have conducted high quality research about bone morphology changes in cavus foot. Their research results indicate that the TN coverage angle (Figure 7) plays an important role in evaluating the effect of cavus foot correction.…”
Section: Radiological Evaluationmentioning
confidence: 99%